Case of olmsted syndrome with essential thrombocytosis misdiagnosed as acrodermatitis enteropathica - Filiz Topaloglu Demir; Ceyda Çaytemel; Nazlı Caf; Zafer Türkoğlu; Mesut Ayer; Nesimi Büyükbabani (Wolters Kluwer Medknow Publications, 2021)
Olmsted syndrome is a rare genodermatosis. Palmoplantar keratoderma and periorificial keratodermic plaques are the most important clinical findings. Additional findings associated with a large number of systems may accompany such as teeth, nail deformities, alopecia, mental retardation, and bone-joint anomalies. Therefore, it is difficult to make a differential diagnosis from other palmoplantar keratodermas. It also needs to be differentiated from acrodermatitis enteropathica because of periorificial plaques. The absence of regression in lesions with zinc treatment excludes this disease. We present here an Olmsted syndrome case with essential thrombocytosis for the first time.